2013
DOI: 10.1002/jmri.23992
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian imaging by magnetic resonance in adolescent girls with polycystic ovary syndrome and age‐matched controls

Abstract: Purpose To compare ovarian morphology in adolescent girls with and without polycystic ovary syndrome (PCOS) using magnetic resonance (MR) imaging. Materials and Methods In 21 adolescent girls (12–18 years) without and 19 adolescents with PCOS (diagnosis based on excessive hair growth and irregular menstrual cycles) ovarian volume, antral follicle count (AFC) per ovary, and follicle size were evaluated. MR imaging was performed at 1.5 T or 3 T and axial or angled-axial single-shot echo-train spin echo images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 25 publications
6
31
1
Order By: Relevance
“…The accepted definition of PCO is based on transvaginal ultrasound in adults and may not be applicable to adolescents (6) since transabdominal ultrasound is generally used in adolescents and ovarian size may be smaller in affected adolescents with PCOS than in affected adults (7). …”
Section: Introductionmentioning
confidence: 99%
“…The accepted definition of PCO is based on transvaginal ultrasound in adults and may not be applicable to adolescents (6) since transabdominal ultrasound is generally used in adolescents and ovarian size may be smaller in affected adolescents with PCOS than in affected adults (7). …”
Section: Introductionmentioning
confidence: 99%
“…Follicle number and size are also noted to increase with puberty, with a higher number of small follicles during adolescence and young adulthood and a decrease thereafter [84] . Isolated studies have also suggested the use of MRI or Doppler examination for the diagnosis of PCOM [85][86][87][88] . Dewailly et al [79] concluded that, when using transabdominal ultrasonography, an ovarian volume >10 cm 3 should be used because follicle counts become unreliable with this methodology.…”
Section: What Are the Criteria For Pcom In Adolescents?mentioning
confidence: 99%
“…Diverse criteria have been used for defining PCOM in adolescents, 52,56,64–70 which has contributed to widely different estimates of PCOM prevalence in adolescents. It is now clear that current adult PCOM criteria are exceeded in about one-third of normal adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…52,64,6668 Furthermore, several studies indicate that ovarian volume during adolescence is larger than that of the normal adult: for example, the median for the normal upper limit of mean ovarian volume during adolescence according to studies to date approximates 12 cc (Table 5). 52,56,6670,72,73 Thus, application of adult criteria for PCOM to adolescents seems very problematic.…”
Section: Discussionmentioning
confidence: 99%